Mannanase Production By Aspergillus Niger IBRL F16.A4 Using Palm Kernel Cake As Substrate - Khulidin, Khairul Asfamawi (2012)
The aim of present study was to detemine the favtors influencing the mannanase production by locally isolated strain, Aspergillus niger IBRL F16.A4 using palm kernel cake as a carbon source.Palm kernel cake (PKC) is an agro-indusstrial by-product obtained after extraction of oil palm from oil palm seeds.PKC was used widely in the animal feed industry but has limited used in poultry feed due to its high fiber and low protein contents.Almost 60% of the fiber content is a mannan.By degradation of mannan using microbial its seem suitable to use as poultry feed. PKC was used as a substrate in semi solid formentation (SmF) by locally isolated strains and their feasibility for mannanase enzyme, glucosamine and mannose production.The potential isolated were obtained from varrious sources such as peat soils, rotten oil palm trunks and raw PKC.The sources were randomly obtained from Ladang United Plantation (UP), Jenderata, 364 Hutan Melintang, Perak, Malaysia.